A citation analysis of the Philippine Sociological Review, 1953-2007 - Vinagrera, Emmanuel R.; Faderon, Rosalie B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2009)
Citation analysis provides an objective supplementary tool for the development of collection management policies. Journals are subject-specific and are indicative of the discourse in the subject field.
The present study implemented citation analysis on the written materials and their corresponding citation lists found in the Philippine Sociological Review articles during the period of 1953-2007. Effectively, this entailed the extraction, counting, and tabulation of PSR written works and their bibliographies as main source of data for the study. The produced raw data were encoded into a database software program in preparation for data analysis and the construction of the citation index. Descriptive statistics were implemented to characterize the gathered data.
The major findings of the study were: the most cited titles in the PSR were the following: Sociology: A Text With Adapted Readings by Leonard Broom ad Philip Selznick with 8 citations (0.25 of total citations), followed Census of the Philippines, 1948 with 7 citations (0.22), Elements of Social Organization by Raymond Firth with 6 citations (0.19), Reciprocity in the Lowland Philippines by Mary Racelis Hollnsteiner with 6 citations (0.19), and Explorations in Social Theory and Philippine Ethnography by Raul Pertierra with 6 citations (0.19); the most cited material type was the monograph with 1,950 citations (45.89), followed by journal article with 1,089 citations (25.63), and book article with 532 citations (12.52); the most cited author in the PSR were the United Nations and Raul Pertierra with 26 citations (0.63) each, followed by Frank X. Lynch with 22 citations (0.53); Philippine Sociological Review was the most cited journal title with 95 citations (8.64), followed by Philippine Studies with 30 citations (2.73), and American Journal of Sociology, with 27 citations (2.46); the predominant country of publication for citations in the PSR was the United States, with 1,544 titles (47.92), followed by the Philippines with 1,117 (34.67) titles, and England with 264 titles (8.19); English titles comprised the majority of citations, with (3,180 citations, 98.51) written in English; the mean and median age of cited materials were 6 years, while the mode age was 0; the core of journals for Philippine sociology included the following: Philippine Sociological Review, Philippine Studies, American Journal of Sociology, and American Sociological Review.
Vita.
Thesis (Bachelor of Library and Information Science)
Part II - Citation index to the Philippine Sociological Review, 1953-2007.
Keywords: Bibliographical citations